PENGARUH PENGETAHUAN DAN KETERAMPILAN TERHADAP PRESTASI KERJA PEGAWAI PADA MTSN MODEL SUNGAI PENUH: PEBI JULIANTO, S.Sos., MM. - Pebi Julianto (JURNAL ADMINISTRASI NUSANTARA, 2018)
The Influence of Knowledge and Skill on Work Performance at MTsN Model Sungai Penuh. This Research aims to conduct a study on The Influence of knowledge and skill on work performance at MTsN Model Sungai Penuh. The Research was done at MTsN Model Sungai Penuh by method used are kuantitatif method with number of respondens 12 people. The research instrument is the research himself and the collection of data through quesionnaires.The Influence of knowledge and skill on work performance at the MTsN Model Sungai Penuh cover Location Of Knowledge, personal skills, reasoning for Ability, understand of ability, values presense and conviction. Conceptual Skills, human skills, technical skills. And work performance consists of work quality, the quality of labor, toughness, attitude. An analytical tool used in this study is the likers, Analyse doubled linear regersa, Koefisien Determinant and test of T with data processing use application program of SPSS version 0.16